Chapter Ricchezza e proprietà in una città levantina: Bari tra Cinque e Settecento - Sardone, Sergio (Datini Studies in Economic History, 2020)
This work offers a descriptive and quantitative picture of the property owned by the socio-economic elite of Bari, the only one of the three present great cities of Southern Italy analysable for the Modern Age, given the exemption granted to Naples and Palermo as capitals of the kingdoms of Naples and Sicily. The analysis on the 1598 apprezzo and the 1753 catasto has allowed to identify and estimate the wealth of the wealthiest families of Bari, and to show the social composition of its main families. From this analysis it emerged also that, during this century and a half, the number of patrician families in Bari halved in favor of those that "lived nobly", with more substantial assets to replace the patriciate, among them those of foreigners from Ferrara and Lombardy.